The Impact of Digital Media Integration on Geography Learning Outcomes in Indonesian High Schools - Makhroza Husna; Nuriza Dora (Journal of General Education and Humanities, 2025)
This study explores how digital media enhances geography learning in Indonesian high schools, specifically focusing on SMA Swasta Budi Agung Medan. In the context of global advancements in educational technology, the integration of digital media in geography education has become increasingly relevant, particularly given the subject’s emphasis on spatial and visual understanding. This research aims to examine the role of digital media in supporting geography learning and to identify the challenges teachers face during its implementation. A qualitative descriptive approach was used, involving interviews with teachers, students, and school administrators at SMA Budi Agung Medan. The findings reveal that digital tools such as Quizizz, Wordwall, and Google Earth are actively used and have increased student motivation, engagement, and comprehension of complex geographical concepts. However, several challenges were identified, including limited access to digital devices among students, insufficient teacher readiness to integrate technology effectively, and difficulties maintaining classroom discipline during interactive sessions. The study concludes that while digital media significantly enriches geography learning, its success depends on improving infrastructure, providing continuous professional development for teachers, and adopting effective classroom management strategies. These findings offer valuable implications for policy development, teacher training programs, and curriculum planning to optimize the integration of digital media in geography education.